The Effects of Fertilization with Dried Spent Coffee Grounds and their Extracts on Germination and Growth of Broad Bean (Vicia faba L.) and Pea (Pisum sativum L.) Plants - Elareffi, Amna; Alshareef, Ibraheem (Journal of Pure & Applied Sciences, 2024)
This study evaluated the effects of fertilization with spent coffee grounds on soil properties, as well as the growth and productivity of broad bean (Vicia faba L.) and pea (Pisum sativum L.) plants. The study consisted of two experiments: the first conducted in Petri dishes and the second in pots. In the first experiment, four concentrations of aqueous coffee extracts (ACE) were tested (25%, 30%, 50%, and 75%), with distilled water serving as a control treatment. Radicle and plumule lengths were measured until the eighth day of the experiment.For most concentrations, the germination percentage of broad beans was higher than that of peas. In beans, germination decreased as ACE concentration increased, with the highest germination rate observed in the control treatment (94.4%) and the lowest in the highest concentration (58.33%). Conversely, for peas, the highest germination rate was recorded at the highest concentration (77.77%), and the lowest at 30% concentration (55.55%). Radicle length in peas was consistently higher in the control treatment, while results for beans varied across treatments.In the second experiment, 900 grams of soil were placed in each pot, and spent coffee grounds were added at the following rates: 0% (control), 2.25%, 4.5%, and 6.5%. Plant height and the number of leaves per plant were measured over five weeks. The responses of the two plants to spent coffee grounds differed. For beans, the highest plant height was observed at 2.25%, while the lowest was at 4.5%; a similar trend was noted for peas. In terms of leaf number, the highest count for peas occurred at 6.5%, while for beans, the largest number of leaves was observed at 2.25%.These findings provide valuable insights into the potential use of spent coffee grounds as an organic fertilizer, highlighting variable effects on different plant species and growth parameters.